Dependence of russian’s gross domestic product on consolidated budget expenditures - A. Tatuev, Arsen (2018)
The article is devoted to the most pressing issues of social development at the modern stage. Is considered social activities of states, which was formed into an autonomous system of government functions. It is noted that in the structure of spending priorities shift toward funding of national defense, social policy and the national economy, while funding for health and education slows down. This paper examines the impact of expenses of the Consolidated budget of the Russian Federation in the gross domestic product.